EDUKASI PEMANFAATAN DIGITAL MARKETING UNTUK MENGEMBANGKAN DAN PEMASARAN BATIK DESA PURWO BAKTI - Yanti, Vivi; Afriyani, Risti; Risman, Ahmad; Putra, Yuda; Azzahra, Chairunnisa (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
The batik industry in Purwo Bakti Village, Jambi, has great growth potential. However, the batik artisans are still constrained in marketing their products widely. Digital marketing education aims to equip batik artisans with the knowledge and skills to market their products using digital platforms. Education is carried out using training and mentoring methods. The training materials include an introduction to digital platforms, interesting content creation techniques, and digital marketing strategies. After attending the education, the batik craftsmen can create accounts and manage digital platforms, create interesting content to promote batik products and carry out digital marketing strategies by utilizing social media Facebook, WhatsApp and Instagram.